The Impact of Rural Pensions in China on Labor Migration - Eggleston, Karen (Published by Oxford University Press on behalf of the World Bank, 2019)
We study the impact of China’s new rural pension program on promoting migration of labor by applying a regression discontinuity analysis to this new pension program. The results reveal a perceptible difference in labor migration among adult children whose parents are just above and below the age of pension eligibility: The adult children with a parent just attaining the pension-eligible age are more likely to be labor migrants compared with those with a parent just below the pension-eligible age. We also find that with a pension-eligible parent, the adult children are more likely to have off-farm jobs. These abrupt changes in household behavior at the cutoff suggest that these households are credit constrained. In addition, we find that the pension’s effect on migration is greater among adult children with a parent in poor health; pension-eligible elderly report that they are more likely to use inpatient services when needed and less likely to rely on adult children for care when they are ill. These results suggest that (expectations regarding) providing care for elderly parents has constrained labor migration from China's rural areas to some extent, and that the new rural pension program has helped to relax this constraint.